DIFFUSIVE DISSOLUTION IN TERNARY SYSTEMS: ANALYSIS WITH APPLICATIONS TO QUARTZ AND QUARTZITE DISSOLUTION IN MOLTEN SILICATES - AN EXPERIMENTAL STUDY OF SOLUBILITIES AND MECHANISM - Liang Y. (My University, 1999)
Exact solutions to equations governing isothermal diffusive dissolution of a crystalline slab in a ternary liquid were obtained to include the effect of coupled chemical diffusion in the liquid. These analytical results, supplemented by approximate solutions valid for slow dissolving, provide new insights into the characteristics of diffusive dissolution in ternary systems. Dissolution rate is proportional to square root of time in diffusive dissolution. The coefficient of proportionality is a function of diffusion coefficients, liquidus relation, melt composition at the crystal-melt interface, and compositions of the dissolving crystal and starting melt. In the limit of slow dissolving, the dissolution rate can be written in terms of three dimensionless parameters that are functions of the aforementioned parameters. Dissolution rate is proportional to the diffusion rate of the slow eigen component in the melt when the diffusion rate of the minor eigen component is much slower than the diffusion rate of the major eigen component.Laboratory experiments of diffusive dissolution of single crystals and polycrystalline aggregates of quartz in a haplodacitic melt (25 wt.% CaO, 15 wt.% Al2O3, and 60 wt.% SiO2) were conducted at 1500°C and 1 GPa. Measured dissolution distances (Xb, in microns) are proportional to the square root of experimental run time (t, in seconds), Xb = -0.620 (+/-0.019) √t. Chemical concentration profiles measured from quenched melts are invariant with time when displayed against the distance (measured from the crystal-melt interface) normalized by the square root of time. The melt compositions at the crystal-melt interface, extrapolated from the measured diffusion profiles in the quenched melts, are within 0.2 wt.% of the independently measured quartz liquidus in the ternary CaO-Al2O3-SiO2 at 1500°C and 1 GPa. These results suggest that crystal and melt are in chemical equilibrium at their interface shortly after the onset of dissolution. Diffusive dissolution of quartz and quartzite is characterized by slow dissolving. Using quartz liquidus as one of the boundary conditions, it has been shown that the calculated dissolution distances and concentration profiles are in good agreement with the experimentally measured ones. Coupled diffusion played an essential role in quartz and quartzite dissolution in haplodacitic to haplobasaltic melts, and is likely to play an important role in diffusion-limited kinetic processes such as crystal growth and dissolution in natural melts of basaltic-rhyolitic compositions.